Isolation and nitrogen removal efficiency of halophilic heterotrophic nitrifying bacteria, Alcaligenes strains SRNB23 and SRNB35 - Chankaew, Sunipa; Sangnoi, Yutthapong; O-Thong, Sompong (Asia-Pacific Journal of Science and Technology, 2024)
The halophilic heterotrophic nitrifying bacteria play a significant role in mitigating the toxicity of inorganic nitrogen compounds, namely ammonia, nitrite, and nitrate in shrimp production systems. Two strains of heterotrophic nitrifying bacteria, namely strain SRNB23 and strain SRNB35, were obtained from sediment samples collected from a pacific white shrimp farm. The microorganisms were classified as Alcaligenes faecalis, with a similarity value ranging from 91% to 98%. The findings indicated that the ammonium removal effectiveness of SRNB23 and SRNB35 was 91.75% and 91.21%, respectively. The optimal proportion of the SRNB23 and SRNB35 mixture was determined to be 30% SRNB23 and 70% SRNB35. The observed ratio exhibited an ammonium removal effectiveness of 59.72%. As a result, sodium citrate has been identified as the preferred carbon source for SRNB23, whereas sucrose has been found to be the best carbon source for SRNB35. Ammonium sulfate was shown to be the most effective nitrogen source for both strains. The C/N ratio of SRNB23 and SRNB35 was found to be 16 and 2, respectively, indicating their respective ideal conditions. Subsequently, an analysis was conducted on both individual bacterial strains and bacterial mixtures in order to assess their efficacy in the treatment of wastewater originating from a shrimp farm, characterized by an ammonium concentration ranging from 461 to 467 mg-N/L. The findings indicated that the combination of SRNB23 and SRNB35 exhibited the most notable efficacy in removing ammonium, with an efficiency rate of 63.07%.